Trace inequalities for positive semidefinite matrices - Choudhury Projesh Nath; Sivakumar K.C. (Discussiones Mathematicae - General Algebra and Applications, 2017)
Certain trace inequalities for positive definite matrices are generalized for positive semidefinite matrices using the notion of the group generalized inverse.